Pricing and lot-sizing policies for products with demand under Veblen effect - Agrawal A.K.; Gupta A.A.; Vora M.K. (My University, 2025)
Veblen products are luxury goods possessed by the persons to mostly exhibit their pride in the society and their demand increases with the increase in the price. For these products, constituting a sizable share of the market, no work is found in the available literature to determine inventory management policies. The present paper, besides doing so, studies the effect on the inventory policy with changes in inventory cost parameters for some demand profiles (Leibenstein 1950) for a single retailer. Sensitivity analysis demonstrates that optimal price for Veblen products for the maximum profit occurs only on those parts of demand curve that follow the Law of Demand (Marshall 1898) and will not be affected by the changes made either to holding cost rate or ordering cost except that to the unit cost. However, optimal inventory policy is found to get affected with the change in all the three parameters. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.